2012
DOI: 10.1001/archgenpsychiatry.2012.934
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Weight Gain With Olanzapine

Abstract: CONTEXT Iatrogenic obesity caused by atypical antipsychotics increases the rate of death from all causes. Olanzapine is a commonly prescribed atypical antipsychotic medication that frequently causes weight gain. To our knowledge, the neural correlates of this weight gain have not been adequately studied in humans. OBJECTIVE To test the hypothesis that olanzapine treatment disrupts the neural activity associated with the anticipation and receipt (consumption) of food rewards (chocolate milk and tomato juice). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 91 publications
3
53
0
1
Order By: Relevance
“…Dopamine D1 and D2 receptor antagonism through their impact on the reward system may also play a role, as it has recently been shown there is an increased anticipatory reward responsivity toward food reward in the inferior frontal cortex, striatum, and anterior cingulate cortex during olanzapine treatment (Mathews et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine D1 and D2 receptor antagonism through their impact on the reward system may also play a role, as it has recently been shown there is an increased anticipatory reward responsivity toward food reward in the inferior frontal cortex, striatum, and anterior cingulate cortex during olanzapine treatment (Mathews et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SGAs, including olanzapine, have been suggested to deteriorate the pre-existing hedonic alterations (enhanced anticipation of food reward) in schizophrenia patients (Elman et al, 2006;Mathews et al, 2012). However, to the best of our knowledge, the role of rewarding system through ghrelin signalling in SGA-induced weight gain has not yet been reported.…”
Section: Ghrelin Signalling and The Rewarding System In Sga-induced Wmentioning
confidence: 95%
“…•OLA-treated patients gained substantial weight, mediated by an increase in caloric intake (27.7 %) •No change in diet composition, REE, or physical activity Theisen et al (2003) Cross-sectional (Leadbetter et al 1992;Treuer et al 2009), increases in appetite and food intake (Fountaine et al 2010;Gothelf et al 2002;Roerig et al 2005;Mathews et al 2012), and poor dietary choices (McCreadie et al 1998). We review these studies below, according to population (i.e., healthy controls versus patients), AAP, and comparison group (Table 1).…”
Section: Anthropometric Measuresmentioning
confidence: 99%
“…Thus, AP-naïve individuals or healthy participants, having never been exposed to APs, can be expected to show the greatest susceptibility to metabolic side effects of AAPs and studies using such individuals allow us to evaluate metabolic side effects independent of psychotic illness and previous AP usage. Three studies exist involving OLA given to healthy subjects; all demonstrate increased body weight with associated increases in hunger or feeding (Fountaine et al 2010;Roerig et al 2005;Mathews et al 2012). Roerig et al (2005) demonstrated that 37.5 % of healthy participants given OLA had increased hunger scores measured by a visual analog scale (VAS) accompanied by an average weight gain of 2.25 kg.…”
Section: Patients With Psychotic Illness Compared To Healthy Controlsmentioning
confidence: 99%
See 1 more Smart Citation